2008
DOI: 10.1152/jn.00963.2007
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and Spinal Modulation of Antagonist Coactivation During a Submaximal Fatiguing Contraction in Humans

Abstract: This study investigates the control mechanisms at the cortical and spinal levels of antagonist coactivation during a submaximal fatiguing contraction of the elbow flexors at 50% of maximal voluntary contraction (MVC). We recorded motor-evoked potentials in the biceps brachii and triceps brachii muscles in response to magnetic stimulation of the motor cortex (MEP) and corticospinal tract (cervicomedullary motor-evoked potentials--CMEPs), as well as the Hoffmann reflex (H-reflex) and maximal M-wave (Mmax) elicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 51 publications
6
73
1
Order By: Relevance
“…This specific encoding leads to the minimization of antagonist muscles activation and improves the energetic efficiency of the muscle contraction (Baratta et al 1988;Carolan and Cafarelli 1992;Hakkinen et al 2000;Bru and Amarantini 2008). This result is in agreement with previous studies that evidenced that central mechanisms are involved in the regulation of agonist and antagonist muscles activations (De Luca and Mambrito 1987;Mullany et al 2002) and corroborates the hypothesis of a distinct central control of antagonist muscles (Levenez et al 2008). In addition, our results showed that the cortical control of antagonist muscles differed between groups specifically in the direction of contraction (flexion) in which the antagonist muscles corresponded to the prime-mover muscles (i.e., knee extensors) of the training task (squats) usually used by ST participants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This specific encoding leads to the minimization of antagonist muscles activation and improves the energetic efficiency of the muscle contraction (Baratta et al 1988;Carolan and Cafarelli 1992;Hakkinen et al 2000;Bru and Amarantini 2008). This result is in agreement with previous studies that evidenced that central mechanisms are involved in the regulation of agonist and antagonist muscles activations (De Luca and Mambrito 1987;Mullany et al 2002) and corroborates the hypothesis of a distinct central control of antagonist muscles (Levenez et al 2008). In addition, our results showed that the cortical control of antagonist muscles differed between groups specifically in the direction of contraction (flexion) in which the antagonist muscles corresponded to the prime-mover muscles (i.e., knee extensors) of the training task (squats) usually used by ST participants.…”
Section: Discussionsupporting
confidence: 92%
“…Antagonist muscles participate in joint stiffness and stability (Basmajian and De Luca 1985;Miller et al 2000;Stokes and Gardner-Morse 2003;Centomo et al 2008;Rao et al 2009), protect the articulation by lowering tension in the ligaments (for review, see Remaud et al 2007) and facilitate movement accuracy (Corser 1973;Tanaka 1974;Gribble et al 2003). Although prior studies have emphasized the important role of central mechanisms for the regulation of agonist and antagonist muscles activations (De Luca and Mambrito 1987;Mullany et al 2002;Levenez et al 2008), no study has directly investigated the brain correlates of the modulation of antagonist muscles activation during human voluntary contractions.…”
Section: Introductionmentioning
confidence: 99%
“…However, nerve stimulation presents potential methodological limitations for some muscles. For instance, obtaining a H-reflex from biceps brachii muscle can be difficult to obtain at rest 49 . Furthermore, stimulating the musculocutaneous nerve over the brachial plexus leads to contraction of both agonist and antagonist muscles 32 , inducing the erroneous evaluation of the voluntary activation level.…”
Section: Discussionmentioning
confidence: 99%
“…The authors indicated that these adaptations could be associated with a specific encoding of antagonist muscles activation through cortical oscillations. In addition, Lévénes et al [27] observed that excitatory drive to the motor neuron pool of the antagonist muscle is increased during fatigue of the agonist muscle, and the different behavior of the Hoffman-reflex and cervicomedullary motor evoked potentials during the fatiguing action in the antagonist muscle, suggests that the level of coactivation is likely under the control of supraspinal rather than spinal mechanisms.…”
Section: Discussionmentioning
confidence: 99%